(untitled) (Polis (Santiago), 2018)
This article explores a possible explanation to the phenomenon of ruptures in chilean political parties, in the weakening of tacit collaborative agreement of the parties’ elite. We consider the assumption that formation of party elites corresponds to a way of the performance of leadership within a collaborative framework which parties are. As a way to verify this approach we analyzed three cases of parties’ dissagregation from 2007 to 2009.